PENGARUH HUMAN RELATIONSHIP DAN LINGKUNGAN KERJA TERHADAP KINERJA YANG DIMEDIASI OLEH ETOS KERJA KARYAWAN DI PT LOTTE MART WHOLESALE MEDAN - Annisa, Eka Dini; Sabrina, R; Bahri, Syaiful (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
This study aims to determine and analyze the effect of human relationships and work environment with employee work ethic as mediation at PT Lotte Mart Wholesale Medan. This study has a sample of 44 respondents by collecting data through interview techniques and distributing questionnaires. The research data was processed using Smart PLS to test 7 hypotheses in the study. The results of this study prove that human relationships positively and significantly affect employee performance, the work environment negatively and insignificantly affects employee performance, and human relationships positively and significantly affect employee work ethic. The work environment negatively and insignificantly affects work ethic and work ethic positively and significantly affects performance. Human relationship positively and significantly affects employee performance through work ethic and work environment negatively and insignificantly affects employee performance work ethic in employees of PT Lotte Mart Wholesale Medan.